2016
DOI: 10.15406/aowmc.2016.04.00109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BMI and Body Fat Percentages between National Level Teenage Swimmers and Controls

Abstract: Swimming is a popular sport in the world which competed at many different levels. Anthropometric parameters in teenagers including swimmers in Sri Lanka are not well documented. It is important to study on swimming and its effect on BMI and body fat levels because more children taking up swimming at school at competition levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
2
1
1
Order By: Relevance
“…Moreover, the same study suggested that BF% is a predictor of swimming performance in women [ 64 ]. Conversely, a more recent study of 90 female teenage national level swimmers (aged 13 to 19 years) suggested lower average BMI (19.0 kg/m 2 ) and BF% (18.2%) compared to our results [ 65 ]. These apparently divergent results may be reconciled by age differences or preparedness and competition type and level.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the same study suggested that BF% is a predictor of swimming performance in women [ 64 ]. Conversely, a more recent study of 90 female teenage national level swimmers (aged 13 to 19 years) suggested lower average BMI (19.0 kg/m 2 ) and BF% (18.2%) compared to our results [ 65 ]. These apparently divergent results may be reconciled by age differences or preparedness and competition type and level.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, an association was observed between the duration of PA at school in the form of PE lessons and the incidence of excessive adipose tissue content. The significant difference in the percentage of body fat content that was observed between children of different levels of PA was also confirmed by other studies [60][61][62][63][64].…”
Section: Discussionsupporting
confidence: 82%
“…Zaobserwowana przez nas istotna różnica w procentowej zawartości tkanki tłuszczowej pomiędzy dziećmi z klas pływackich a dziećmi nietrenującymi znajduje potwierdzenie w pracy Dessnayake i wsp. [21]. Olsztyńskie dzieci z grupy badanej i kontrolnej wykazywały podobieństwo pod względem innych zmiennych antropometrycznych, jednak w pracach dotyczących porównań dzieci trenujących pływanie i ich rówieśników stwierdzono również istotne różnice w masie ciała i wysokości ciała [22,23].…”
Section: Omówienieunclassified